Applying recommended definition of aggressive prostate cancer: a validation study using high-quality data from the Cancer Registry of Norway. (2nd January 2023) - Robsahm, T. E.; Tsuruda, K. M.; Hektoen, H. H.; Storås, A. H.; Cook, M. B.; Hurwitz, L. M.; Langseth, H.
Abstract: Background: The Prostate Cancer Cohort Consortium (PC3) Working Group proposed a definition for aggressive prostate cancer (PC) for aetiologic epidemiologic research. We aimed to validate this definition as well as a second approach utilising only information on stage at diagnosis. Methods: First primary PCs diagnosed 2004 − 2009 in the population-based Janus Serum Bank (JSB) cohort were identified by linkage to the population-based Cancer Registry of Norway (CRN) ( n = 3568). The CRN and Norwegian Prostate Cancer Registry provided clinicopathological data for these cases. Approach 1 classified PC as aggressive if it was clinically T4, or N1, or M1, or had a Gleason score ≥8 at diagnosis (as proposed). Approach 2 classified PC as aggressive if CRN stage at diagnosis was 'regional spread' or 'distant metastases'. Both approaches were validated by calculating the sensitivity and positive predictive value (PPV) against PC-death within 10 years of diagnosis. Results: Overall, 555 died from PC within 10 years. Approach 1 classified 24.7% of cases as aggressive and 13.6% were unclassified due to missing information. Approach 2 classified 19.6% as aggressive and 29% were unclassified. Sensitivity was highest for Approach 1 (0.76, 95% CI: 0.72 − 0.80 vs 0.69, 95% CI: 0.64 − 0.73), while PPVs were similar for both approaches (0.43, 95% CI: 0.40 − 0.46 and 0.40, 95% CI: 0.36 − 0.44). We observed similarly high sensitivity and higher PPVs than those reported by the PC3 Working Group. Conclusions: The proposed definition of aggressive PC was applicable and valid in the JSB cohort. Stage at diagnosis can be useful if data on cTNM or Gleason score is unavailable.